Ibn Khaldun’s Fourteenth Century Views on Bureaucracy (American Journal of Islam and Society, 1987)
IntroductionAdam Smith observed in his Wealth of Nations in 1776 that kings-or inmy terminology the early bureaucratic leaders - existed already in “that rudestate of society which precedes the extension of commerce and the improvementof manufactures” (Smith 1976: 907). Max Weber considered bureaucracya necessary precondition for the development of society (Mieczkowski 1984:105-06; Zinam 1984: 77-78) providing the element of functional organizationand purpose. However, since power corrupts, it comes as no surprise thateven the early bureaucratic leaders developed some dysfunctional traits, thatcorruption all too frequently became the prevalent mode of operation, andthat the benign functional bureaucratic organizations, or ”borgs,” became inmany cases transformed into “dysborgs,” or the dysfunctional bureaucraticorganizations. An analysis of dysborgs and of some of their implications isoffered in Mieczkowski and Zinam, Bureaucracy, Ideology, Technology: Qualityof Life East and West (1984), and the terminology that is used in the presentessay to interpret historical views, with their original concepts, will befrom the Mieczkowski and Zinam book.Because the rudimentary bureaucratic organization developed early, someastute observers found already in remote times that bureaucracy is not alwaysbenign. It was, therefore, with great interest that I discovered one such observerwho had been neglected by Western historians of economic thought, exceptfor a footnote and a bare small-print mention in Joseph Schumpeter‘s Historyof Economic Analysis (1954: 136, 788), a footnote in Colin Clark’s Conditionsof Economic Progress (1957: 6), and a footnote in Barry Gordon’sEconomic Analysis Before Adam Smith (1957: 121). The writer in questionwas an Arab historian and philosopher, Ibn Khaldun (1332-1406), who coveredmany topics of interest to economists, and who in some respects was headof the founder of the science of economics, Adam Smith. Such occasional ...